MIDWIFERY CARE FOR IMPLANT ACCEPTOR OF MRS. C IN THE WORKING AREA OF PEUKAN BADA COMMUNITY HEALTH CENTER, THE REGENCY OF ACEH BESAR IN 2025 - Seriana, Irma; Khusna, Alfi; Anita, Anita (Journal of Midwifery and Community Health (JMCH), 2025)
The main problem facing Indonesia today is its still-high population growth rate. This problem can be addressed using effective, long-term contraceptives. One recommended and considered effective contraceptive program is the Long-Term Contraceptive Method, which is an implant. The number of long-term contraceptive acceptors in Indonesia is still low, namely below 5%, including in the Regency of Aceh Besar. The purpose of this study was to provide midwifery care to the implant acceptor, namely Mrs. C (25 years old), in the working area of the Peukan Bada Community Health Center (Puskesmas), Aceh Besar Regency, and document this using the midwifery documentation method (SOAP). Midwifery care for the implant acceptor was provided three times: pre-insertion, insertion, and post-inser